A three-gene expression score for predicting clinical benefit to anti-PD-1 blockade in advanced renal cell carcinoma - Betancor, Yoel Z.; Ferreiro-Pantín, Miriam; Anido-Herranz, Urbano; Fuentes-Losada, Mar; León-Mateos, Luis; García-Acuña, Silvia Margarita; Vaamonde-Rodríguez, Vanessa; García-Pinel, Beatriz; Cebey-López, Víctor; Villaverde-Viaño, Rosa; Lombardía-Rodríguez, Helena; Kotrulev, Martin; et al. (Frontiers in Immunology, 2024)
In the advanced renal cell carcinoma (RCC) scenario, there are no consistent biomarkers to predict the clinical benefit patients derived from immune checkpoint blockade (ICB). Taking this into consideration, herein, we conducted a retrospective study in order to develop and validate a gene expression score for predicting clinical benefit to the anti-PD-1 antibody nivolumab in the context of patients diagnosed with advanced clear cell RCC enrolled in the CheckMate-009, CheckMate-010, and CheckMate-025 clinical trials. First, a three-gene expression score (3GES) with prognostic value for overall survival integrating HMGA1, NUP62, and ARHGAP42 transcripts was developed in a cohort of patients treated with nivolumab. Its prognostic value was then validated in the TCGA-KIRC cohort. Second, the predictive value for nivolumab was confirmed in a set of patients from the CheckMate-025 phase 3 clinical trial. Lastly, we explored the correlation of our 3GES with different clinical, molecular, and immune tumor characteristics. If the results of this study are definitively validated in other retrospective and large-scale, prospective studies, the 3GES will represent a valuable tool for guiding the design of ICB-based clinical trials in the aRCC scenario in the near future.